Short-term Venous Patency after Implantation of Permanent Pacemakers or Implantable Cardioverter Defibrillators - Nakae, Takeshi, MD; Enjoji, Yoshihisa, MD; Noro, Mahito, MD; Sugi, Kaoru, MD (Journal of Arrhythmia, 2010)
Abstract There is little information on venous patency after pacing leads are inserted in veins during pacemaker or implantable cardioverter defibrillator (ICD) implantation. Herein we present a report on venous patency during the immediate postoperative period after permanent pacemaker or ICD implantation. Subjects and Methods: Twenty-five patients underwent a permanent pacemaker or ICD implantation by venous puncture method, and venography was performed 1 week later. We assessed the pacemaker-implantation side, approach used, implanted device, number of implanted leads, and clinical symptoms. Results: Narrowing of the vein was found in 14 patients (56%), including 7 patients (28%) with occlusion. Stenosis and occlusion were seen more in patients with left-sided implantation than those with right-sided implantation (71% vs. 25%, P < 0.05). ICD implantation was more frequently associated with venous stenosis or occlusion than pacemaker implantation (65% vs. 37.5%, P < 0.05). The approach used and the number of leads implanted did not correlate with venous stenosis or occlusion. Six of the 7 patients who developed complete occlusion showed clinical symptoms. Conclusion: Thrombus formation after pacemaker implantation can occur in the acute stage within 1 week. The incidence of venous stenosis or thrombus formation was higher with leftsided implantation and ICD.